2012
DOI: 10.1088/0957-4484/23/28/289502
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanomesh-based devices exhibiting a strong negative differential conductance effect

Abstract: The full text of the corrigendum is available in the pdf provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Devices exhibiting a negative differential conductance (NDC) are also of strong interest for high-frequency applications. With different physical origins, this effect has been predicted in different kinds of graphene nanoribbon or nanomesh junctions [17]- [23], in graphene superlattices [24], in resonant tunneling diodes [25], [26], in FETs [27], and in tunnel FETs [28]. It has been even observed experimentally in a graphene FET as a consequence of ambipolar transport behavior [29].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Devices exhibiting a negative differential conductance (NDC) are also of strong interest for high-frequency applications. With different physical origins, this effect has been predicted in different kinds of graphene nanoribbon or nanomesh junctions [17]- [23], in graphene superlattices [24], in resonant tunneling diodes [25], [26], in FETs [27], and in tunnel FETs [28]. It has been even observed experimentally in a graphene FET as a consequence of ambipolar transport behavior [29].…”
Section: Introductionmentioning
confidence: 93%
“…Assuming the lateral width of the device to be much larger than the channel length, the y-direction can be considered through Bloch periodic boundary conditions [32], [33]. The lattice is split into elementary cells, and by Fourier transform of the operators in (1) (along the Oy-direction), the Hamiltonian (1) is rewritten in the form of decoupled quasi-1-D Hamiltonians for each k y value [23], [26]. The retarded Green's functions of these Hamiltonians are computed in the ballistic approximation.…”
Section: Simulated Device and Transport Modelmentioning
confidence: 99%
“…Hence, antidot barriers enable tight confinement as well as effective transport barriers. theoretical side, several studies support the usefulness of antidot structures for transport devices [20][21][22][23][24]. In Refs.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, in that work, the effects of increasing the number of antidots along the transport direction was systematically studied. Finally, it has been demonstrated that GALs in a pn-junction geometry may be utilized to realize negative differential conductance [24]. Hence, there is by now ample experimental and theoretical evidence for the usefulness of GALs in electronic transport devices.…”
Section: Introductionmentioning
confidence: 99%
“…All other simulation parameters are given in the figure captions. We assume the lateral width of the device to be much larger than the channel length, so that the y direction can be considered through Bloch periodic boundary conditions [9,10]. Now, we summarize the most important features of the transport model used to compute the current density.…”
Section: Device Transport Modelmentioning
confidence: 99%